Practice of Hot Abdominal Compression among Parturient Women at the University College Hospital, Ibadan, Nigeria (2019)
Background: The postpartum period is an important period of excitement with the arrival of the newborn. The body then starts physiological adaptations to revert to the pregnancy states. These physiological adaptations can be associated with some cultural practices like hot abdominal compress (HAC) which may have harmful effects such as hot water burns, abdominal wrinkling and darkening. This study assessed the practice of HAC among mothers seen at the postnatal clinic of the University College Hospital (UCH), Ibadan, Nigeria. Methods: This was a cross-sectional study among 290 postpartum women recruited consecutively at the postnatal clinic in UCH between 1st December 2015 and 29th February 2016. Data collection was by pretested self-administered questionnaire and was analyzed using SPSS version 22.0. p value was set at < 0.05. Results: The participants’ mean age was 31.88 (SD+ 5.1 years), 97.2% of the women had ANC in formal setting and 53.8% had vaginal delivery. Of the 290 participants, 264 (91.0%) were aware of HAC and 51.7% practiced HAC. The return of uterus to normal size (34.7%) and mothers’ encouragements (24.7%) were the commonest reason for practice of HAC. Mothers’ and mothers-in-law’ assisted with HAC in 46.2% and 36.6% of cases, respectively. More vaginally-delivered women practiced HAC (p < 0.001). Conclusion: This study showed that practice of postpartum HAC is high and the reasons for the practice are more of tradition and cultural beliefs. There is need for more studies to better understand this culturally deep-rooted practice.